The Impact of Multimedia Elements on Tablets and Digital Stories in Learning Process Management - Nurjaya; Maulana, Yono; Maulida, Indira Shofia; Bakri; Antonia Junianty Laratmase (Universitas Pendidikan Ganesha, 2024)
Technology is an effective teaching method among educators because it is easier and faster to implement. Switching to traditional methods is very appropriate to apply in the current era of digital technology. The inclusion of multimedia elements into Digital storytelling (PD) has provided innovation in the learning process with the support of mobile technology interaction features. However, using interaction features and multimedia elements such as text and images to create storytelling is still difficult for students and teachers. Meanwhile, elements for evaluating storytelling with technology are still lacking. Research is urgent because of differences in expectations, theory, and reality. The research aims to analyze the reliability of multimedia elements on tablets and digital story evaluation and to determine the correlation of multimedia elements on tablets and digital story evaluation. The research method is a quantitative survey approach. The subjects were students, pupils, teachers, and lecturers totaling 41 people. Data collection techniques with instruments were developed from multimedia indicators, digital stories, and tablets. Instruments were assessed based on a Likert scale from 1-7 points. Analysis techniques were using SPSS Version 25.0 with validation tests, mean, standard deviation, and minimum and correlation values. Research findings show that multimedia, digital stories, and tablet use have high reliability and correlation as well as a positive and significant relationship between all variables in the evaluation. Respondents also assessed multimedia elements in digital stories and tablets. The findings confirm that multimedia elements are at level 5 and can be used in an effective learning process.